Internet technology acceptance factors based on sharing information toward supply chain performance - Ahmed, Abdllah Yahia Moqbile; Mohamed Udin, Zulkifli (2010)
Managers have believed that Internet can enhance SCM decision making by providing on real time information and enabling collaboration between trading partners. Supply Chain Management have a lot of practices depend on information sharing, the Internet has become one of the tools for theses practices which make the operation inside the organization more performance and effective in the same time. O'Keeffe (2001) argues that the internet is playing an important role in exchange information, and strengthening the relationship between suppliers and organization’s managers. Many other researchers stress the need to future research on the impact of internet on supply chain process specifically. Up to date the research on the relationship between the acceptance of internet technology applications factors on the information exchange and its influence on the performance of supply chain management still limited. So that this paper will investigate the internet technology acceptance factors such as trust, ease of use, usefulness, security, self efficacy, self commitment, management support and user technical support as the main antecedent for information sharing among the employees. The paper also will discuss the impact of information sharing towards supply chain management performance. The review of the past research and in depth theoretical review will justify the proposed relationship.